Liver damage in infectious mononucleosis in children - S. V. Khaliullina; F. M. Yakupova; E. I. Nasyrova; K. V. Mikhailova; Yu. A. Raimova; O. A. Nazarova; V. A. Anokhin (Журнал инфектологии, 2024)
The purpose of the study was to evaluate the clinical and laboratory features of infectious mononucleosis with liver damage in children hospitalized in an infectious diseases hospital.Materials and methods. A comparative retrospective study was conducted from January 2018 to June 2021. 200 Medical records of an inpatient were selected by random sampling. Inclusion criteria: age from 1 to 17 years, clinical presentation of infectious mononucleosis, absence of severe concomitant pathology. All patients underwent a standard laboratory examination, additionally determined the DNA of herpes viruses in the blood by PCR. Depending on the presence of cytolysis syndrome (ALT level > 31 U/l), all patients were divided into 2 groups: children with hepatic manifestations of IMN – 80 patients (40%) and without them – 120 (60%). Statistical analysis of the obtained results was carried out using the statistical program Statistica 8 (USA).Results. Epstein – Barr virus was the cause of the development of IMN clinic in 59% (118/200) of cases of monoinfection and in 14.5% (29/200) in combination with other herpesviruses. All participants in the study had moderate disease. An increase in the level of alanine aminotransferase (ALT) above 150 U/L was recorded in 9.5% (19/200) of the examined, no one had more than 1000 U/L, the median was 72.5 (MKR 48–138.5) U/L. Liver damage was more often recorded in children older than 3 years, girls predominated (53.8%, p = 0.017). In patients with liver damage, the following were recorded: moderately severe fever and lymphadenopathy (p < 0.05), hepatosplenomegaly (p < 0.001), lymphocytic leukocytosis (p < 0.05), thrombocytopenia (p < 0.001), atypical mononuclear cells were detected more often (p < 0.001), less often an increase in the level of CRP (p = 0.008).Conclusions. Our study showed that liver damage in IMN is registered in 40% of hospitalized children. Obviously, children with moderate forms of IMN need laboratory and instrumental monitoring of the state of the hepatobiliary system and appropriate correction of therapy.